2008
DOI: 10.1007/s10787-007-1602-4
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of Kalpaamruthaa, a herbal preparation on adjuvant induced arthritis in wistar rats

Abstract: The present study was performed in order to establish the efficacy of Kalpaamruthaa (KA), a modified indigenous Siddha preparation in adjuvant induced arthritic rat (AIA) model with reference to mediators of inflammation (lysosomal enzymes) and its effect on proteoglycans. Albino rats of Wistar strain were divided into seven Groups of six animals each. Arthritis was induced to rats by subcutaneous injection of 0.1 ml of Complete Freund's Adjuvant into the plantar surface of the left hind paw. Group I served as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…We have observed an increase in the rate of this protein in the positive control group. Similar results were obtained by Mythilypriya et al [31] and Abdin et al [32] Also, Moncada et al, [33] Milovanovic et al [34] and Klimiuk et al [35] have observed high values of CRP indicative of active inflammation in the sera of patients suffering from rheumatoid arthritis. In the preventive group we did not observe any change in the rate of the serum CRP indicating that the methanolic extract of Ajuga iva decrease its level.…”
Section: Aime Effect On the Histopathological Changessupporting
confidence: 83%
See 2 more Smart Citations
“…We have observed an increase in the rate of this protein in the positive control group. Similar results were obtained by Mythilypriya et al [31] and Abdin et al [32] Also, Moncada et al, [33] Milovanovic et al [34] and Klimiuk et al [35] have observed high values of CRP indicative of active inflammation in the sera of patients suffering from rheumatoid arthritis. In the preventive group we did not observe any change in the rate of the serum CRP indicating that the methanolic extract of Ajuga iva decrease its level.…”
Section: Aime Effect On the Histopathological Changessupporting
confidence: 83%
“…[31] In the present study we found that the methanolic extract of Ajuga iva has an anti-inflammatory effect by the reduction in volume of edema of the legs and the markers inflammatory like CRP, it removed the overproduction of the protein C, the severity of the signs of arthritis (arthritic score), to decrease the number of the leucocytes, the levels of (ESR) were close to that of the negative reference group. However, other studies are necessary to check the effect of the extract of Ajuga iva on the other serologic parameters and to assess the possible mode of action of these extracts.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The administration of Clerodendrum phlomidis ethanol extract significantly decreased the plasma acid hydrolases in a dose dependent manner. Clerodendrum phlomidis may act by modulating the lysosomal membrane in such a way that it is capable of fusing with the plasma membrane and thereby preventing the discharge of acid hydrolases or by inhibiting the release of lysosomal enzymes (Carevic and Djokic, 1988;Mythilypriya et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The basic understanding of joint disease and development of effective anti-arthritic agents are studied using the experimental arthritic models (Mythilypriya et al 2008). Adjuvant-induced arthritis in rats, characterized by infiltration of synovial membrane and associated with destruction of joints, has been very widely adapted model in pharmaceutical screening which shares a number of clinical and immunological features with human arthritis (Newbould 1963).…”
Section: Introductionmentioning
confidence: 99%